Preparation process of biomass-based carbon nanotube and natural graphite composite negative electrode material
Through the preparation process of biomass-based carbon nanotubes and natural graphite composite materials, the problems of insufficient interface bonding, structural design defects and prelithiation difficulties are solved, and efficient and low-cost negative electrode material preparation is achieved, which improves the circulation stability and first effect of the material, and is suitable for high-energy density lithium-ion batteries.
Patent Information
- Application Number
- CN202510572387.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-06
- Publication Date
- 2025-07-29
AI Technical Summary
The existing carbon nanotube/graphite composite anode materials have problems such as insufficient interface bonding, structural design defects, difficulties in prelithiation and complex preparation processes, resulting in poor cycle stability, low first efficiency and high production costs.
The preparation process of biomass-based carbon nanotubes and natural graphite composite materials, including in-situ growth of carbon nanotubes, surface modification, low-temperature heat treatment and prelithiation treatment, is used to improve the interface binding force of the material, lithium ion diffusion rate and first-time Coulomb efficiency through interface enhancement, structural optimization and simplified process steps.
It significantly improves the interface binding force, lithium ion diffusion speed and first-time Coulomb efficiency of composite negative electrode materials, simplifies production processes, reduces energy consumption, is suitable for continuous production, and meets green manufacturing standards.
Smart Images

Figure CN120389026A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation scheme design of biomass-based carbon nanotube and natural graphite composite anode materials, and specifically relates to a preparation process of biomass-based carbon nanotube and natural graphite composite anode materials. Background Art
[0002] With the wide application of lithium-ion batteries in fields such as electric vehicles and energy storage systems, the development of anode materials with high energy density and long cycle life has become a research hotspot. The theoretical specific capacity of traditional graphite anodes is only 372 mAh / g, which is difficult to meet the requirements of next-generation batteries. Therefore, carbon-based composite materials have become the research focus. However, the existing carbon nanotube / graphite composite anode materials have the following key problems: Insufficient interfacial bonding: The mechanical mixing between carbon nanotubes and graphite particles results in weak interfacial bonding force, which is prone to delamination during cycling, reducing the structural stability; Defects in structural design: Traditional processes are difficult to precisely control the coating density and pore structure of carbon nanotubes, resulting in limited lithium-ion diffusion rate and poor high-rate performance; Difficulty in prelithiation: The low first coulombic efficiency (usually <85%) stems from irreversible capacity loss, and the existing prelithiation technologies are inefficient and prone to introducing impurities; Complex preparation process: Multistep methods (such as separate carbonization and chemical vapor deposition) lead to high production costs and are difficult to scale up.
[0003] The existing technology prepares carbon nanotube / graphite composites by mechanical mixing method, but the interfacial bonding problem is not solved, and the cycle stability is poor; or the chemical vapor deposition method can achieve carbon tube coating, but the process is complex and the cost is high. Therefore, there is an urgent need to develop a preparation process for composite anode materials with strong interfacial bonding, controllable structure, and high first coulombic efficiency.
[0004] Therefore, the existing technology still needs to be further developed. Summary of the Invention
[0005] The purpose of the present invention is to overcome the above technical deficiencies and provide a preparation process of biomass-based carbon nanotube and natural graphite composite anode materials to solve the problems existing in the prior art.
[0006] To achieve the above technical purpose, the present invention provides a preparation process of biomass-based carbon nanotube and natural graphite composite anode materials, including: Step A: Mix the biomass raw material with the catalyst precursor and then perform carbonization treatment to obtain biomass-based carbon nanotubes; Step B: Mix the biomass-based carbon nanotubes with natural graphite, and coat the carbon nanotubes on the surface of graphite particles through an in-situ growth process; Step C: Perform surface modification on the coated composite material to enhance the interfacial bonding force between carbon nanotubes and graphite; Step D: Optimize the pore structure of the composite material using a low-temperature heat treatment process to increase the lithium-ion diffusion rate; Step E: Perform surface passivation on the heat-treated composite material to reduce irreversible lithium-ion consumption; Step F: Mix the passivated composite material with a conductive agent and a binder to prepare an electrode slurry; Step G: Coat the electrode slurry on a current collector and perform drying and rolling processes to obtain a composite negative electrode sheet; Step H: Perform prelithiation on the composite negative electrode sheet to improve the first Coulombic efficiency; Step I: Assemble the prelithiated composite negative electrode sheet into a lithium-ion battery and conduct electrochemical performance tests.
[0007] Specifically, in the step A, the biomass raw material is selected from coconut shells, lignin, straw, or fruit shells, and the catalyst precursor is selected from oxides or salts of iron, cobalt, or nickel.
[0008] Specifically, in the step B, the in-situ growth process uses chemical vapor deposition, and a carbon source gas and a carrier gas are introduced. Carbon nanotubes are grown at 500 - 800 °C. The carbon source gas includes methane and / or ethane, and the carrier gas includes hydrogen and / or argon.
[0009] Specifically, in the step C, the surface modification is performed using plasma treatment or silane coupling agent modification to enhance the interfacial bonding force between carbon nanotubes and graphite.
[0010] Specifically, in the step D, the temperature of the low-temperature heat treatment process is 400 - 600 °C, and it is carried out under the protection of an inert gas to optimize the pore structure and reduce structure collapse.
[0011] Specifically, in the step E, the surface passivation is performed by depositing an amorphous carbon or graphene protective layer using chemical vapor deposition to reduce electrolyte side reactions.
[0012] Specifically, in the step F, the conductive agent is selected from acetylene black, SuperP, or carbon nanofibers, and the binder is selected from PVDF, CMC, or SBR.
[0013] Specifically, in the step H, the prelithiation is performed using the direct contact method with lithium foil or lithium powder and is carried out under the protection of an inert gas to improve the first Coulombic efficiency.
[0014] Specifically, in the step I, the lithium-ion battery uses a liquid electrolyte or a solid electrolyte, and is subjected to charge and discharge cycle tests, rate performance tests, and cycle life tests.
[0015] Specifically, the process uses a continuous production line, including a biomass raw material treatment module, a carbon nanotube growth module, a graphite composite module, a surface modification module, an electrode preparation module, and a battery assembly module.
[0016] Beneficial effects: Through process innovations such as in-situ growth of carbon nanotubes, surface modification, low-temperature heat treatment, and prelithiation, the comprehensive performance of the composite anode material is significantly improved, and the present invention has the following advantages: Strong interfacial bonding force: The carboxyl density on the surface of carbon nanotubes is increased by nitric acid oxidation method, and combined with the modification of KH-550 coupling agent, the interfacial bonding strength is greatly improved; Optimized pore structure: The layer spacing is precisely regulated by low-temperature heat treatment, greatly improving the Li ion diffusion rate; Significant improvement in first efficiency: The amorphous carbon passivation layer and the prelithiation process work together to effectively reduce the irreversible capacity; Simplified and efficient process: The in-situ carbonization-coating integration process reduces energy consumption, simplifies the process steps, and is suitable for continuous production; Environmental friendliness: Without strong acid treatment and water washing processes, it meets the green manufacturing standards. Description of the drawings
[0017] Figure 1 It is a schematic flow chart of the preparation process of the biomass-based carbon nanotube and natural graphite composite anode material provided in the specific embodiment of the present invention. Specific embodiments
[0018] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Based on the embodiments in this application, other similar embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the scope of protection of this application. In addition, the directional terms mentioned in the following embodiments, such as "up", "down", "left", "right", etc., are only references to the directions in the drawings. Therefore, the directional terms used are for illustration rather than to limit the present invention.
[0019] The present invention will be further described below in conjunction with the drawings and preferred embodiments.
[0020] Please refer to Figure 1 , the present invention provides a preparation process of a biomass-based carbon nanotube and natural graphite composite anode material, including: Step A: Mix the biomass raw material with the catalyst precursor and then carry out carbonization treatment to obtain biomass-based carbon nanotubes.
[0021] Specifically, in the said Step A, the biomass raw material is selected from coconut shells, lignin, straw or fruit shells, and the catalyst precursor is selected from oxides or salts of iron, cobalt or nickel.
[0022] It should be further noted that in the said Step A, the present invention designs the following scheme: Biomass raw material: Select coconut shells, lignin, straw or fruit shells, preferably coconut shells, because of their high carbon content (about 45 - 50%) and low ash content. .
[0023] Catalyst precursor: Use oxides or salts of iron (Fe), cobalt (Co) or nickel (Ni), preferably Fe(NO_3)_3. , so it has high catalytic activity and is easy to remove.
[0024] Furthermore, the present invention designs an optimized scheme for the catalyst precursor, including: Catalyst selection: Ferric nitrate (Fe(NO3)3·9H2O, purity > 99.5%), loading amount 0.5wt% (relative to the biomass raw material).
[0025] Loading method: Solution impregnation method (Fe⁺ concentration 0.1mol / L, impregnation time 6h, drying at 120°C for 12h).
[0026] Reason: Fe³⁺ generates Fe3C catalyst nuclei after carbonization, promoting the growth of carbon nanotubes, while too high a loading amount (> 1wt%) is likely to cause carbon nanotube aggregation.
[0027] Carbonization process: Mixing ratio is biomass:catalyst = 100:1 (mass ratio), heat up to 600°C under nitrogen protection, heating rate 5°C / min, keep warm for 2h. This temperature can effectively crack the biomass to generate carbon nanotubes, and at the same time avoid excessive graphitization (> 800°C is likely to cause an increase in tube diameter).
[0028] Furthermore, the carbonization process designed by the present invention specifically includes: Equipment: Tube furnace (nitrogen protection, flow rate 200mL / min), load the raw materials in a graphite crucible (catalyst + biomass = 1:100 w / w).
[0029] Heating program: Heating rate: 5°C / min (to avoid structural defects caused by rapid heating).
[0030] Insulation temperature: 600°C (the optimal temperature for carbon nanotube generation), insulation time 2h.
[0031] Reason: When the temperature > 600 °C, the catalytic activity of Fe decreases, and carbon nanotubes are easily merged into a bundle structure.
[0032] The probability of methane cracking to generate carbon atoms is the highest at 600 °C (the experimentally measured carbon yield: 550 °C = 42% vs 600 °C = 78%).
[0033] Product treatment: The carbonized product is washed with 1 M HCl (60 °C, 2 h) to remove metal oxides, then washed with deionized water until pH = 7, and dried (80 °C, 12 h).
[0034] It can be understood that the biomass raw material is preferably coconut shell because of its high carbon content (compared with straw, the carbonization yield of coconut shell increases by 30%).
[0035] Step B: Mix the biomass-based carbon nanotubes with natural graphite, and make the carbon nanotubes coat the surface of graphite particles through an in-situ growth process.
[0036] Specifically, in the step B, the in-situ growth process uses chemical vapor deposition, and a carbon source gas and a carrier gas are introduced. The carbon nanotubes are grown at 500 - 800 °C. The carbon source gas includes methane and / or ethane, and the carrier gas includes hydrogen and / or argon.
[0037] It should be further noted that in the step B, the present invention designs the following scheme: Carbon nanotube modification: The nitric acid oxidation method (65% HNO3, treated at 60 °C for 2 h) is used to increase the surface carboxyl group (-COOH) and improve the binding ability with graphite.
[0038] In-situ growth process: Use chemical vapor deposition (CVD), the carbon source gas is methane (CH4) (flow rate 50 mL / min), and the carrier gas is hydrogen (H2 (flow rate 100 mL / min), the reaction temperature is 650 °C, and the time is 1 h.
[0039] Optimized parameters: At 650 °C, the decomposition efficiency of CH4 is relatively high, and H2 can inhibit the aggregation of carbon nanotubes to ensure uniform coating.
[0040] It can be understood that 650 °C of the CVD temperature is the preferred value. At this temperature, the methane decomposition rate is the highest (> 95%), and the carbon nanotube yield reaches 25%.
[0041] Step C: Perform surface modification treatment on the coated composite material to improve the interfacial bonding force between the carbon nanotubes and graphite.
[0042] Specifically, in the step C, the surface modification treatment is carried out by plasma treatment or silane coupling agent modification to improve the interfacial bonding force between the carbon nanotubes and the graphite.
[0043] It should be further noted that in the step C, the present invention designs the following scheme: Surface modification: Treatment with silane coupling agent (KH-550). Specific method: The composite material is immersed in KH-550 ethanol solution (concentration 1%), ultrasonicated for 30 min and then dried.
[0044] Mechanism of action: The amino group (-NH2) of KH-550 reacts with the hydroxyl group of the carbon nanotubes to form Si-O-C bonds, enhancing the interfacial bonding force.
[0045] Furthermore, the reaction conditions in the step C of the present invention include: Temperature: 40 °C (to avoid thermal decomposition).
[0046] Time: 30 min (FTIR detection - residual amount of -NH2 < 0.5%).
[0047] Drying: Vacuum drying at 60 °C (to prevent hydrolysis and inactivation).
[0048] Effect: XPS shows that the content of Si-O-C bonds increases to 1.8 at% (for the unmodified sample < 0.3 at%).
[0049] Step D: Optimize the pore structure of the composite material by a low-temperature heat treatment process to improve the lithium ion diffusion rate.
[0050] Specifically, in the step D, the temperature of the low-temperature heat treatment process is 400 - 600 °C and it is carried out under the protection of an inert gas to optimize the pore structure and reduce structural collapse.
[0051] It should be further noted that in the step D, the present invention designs the following scheme: Low-temperature heat treatment: Temperature 500 °C (nitrogen protection), time 2 h, heating rate 3 °C / min.
[0052] Reason for preference: 500 °C can moderately expand the graphite layer spacing (from ~0.34 to 0.37 nm), promoting the diffusion of Li ions, while avoiding the destruction of the graphite structure (>600 °C is prone to cause the collapse of the lamellar structure).
[0053] Furthermore, the low-temperature heat treatment includes: Heating rate: 3 °C / min (to avoid thermal shock and cracking of the graphite layer).
[0054] Pore size regulation: The (002) peak measured by XRD shifts to 2θ = 26.5° (layer spacing d 002Converted from 0.337 nm to 0.342 nm).
[0055] BET analysis: Specific surface area is 120 m² / g (50 m² / g for raw graphite), pore volume is 0.45 cm³ / g (facilitating Li-ion diffusion).
[0056] Step E: Perform surface passivation treatment on the heat-treated composite material to reduce irreversible lithium-ion consumption.
[0057] Specifically, in Step E, the surface passivation treatment uses chemical vapor deposition to deposit an amorphous carbon or graphene protective layer to reduce side reactions of the electrolyte.
[0058] It should be further noted that in Step E, the present invention designs the following scheme: Surface passivation: Deposit an amorphous carbon layer by chemical vapor deposition (CVD).
[0059] Process parameters: Propylene (C3H6) is used as the carbon source (flow rate 30 mL / min), under Ar protection, temperature 400 °C, time 0.5 h.
[0060] Effect: The amorphous carbon layer (preferably with a thickness of 5 nm) can block side reactions of the electrolyte and reduce capacity loss caused by the formation of the SEI film.
[0061] Furthermore, regarding the deposition of amorphous carbon, the present invention designs the following scheme: Carbon source: Propylene (C3H6, purity ≥ 99.9%), flow rate 30 mL / min.
[0062] Temperature: 400 °C (the efficiency of generating C* radicals from propylene cracking is the highest).
[0063] Coating thickness: The layer thickness is 5 ± 1 nm as measured by SEM (too thick will affect Li⁺ diffusion).
[0064] Electrochemical verification: The CV curve shows that the reduction peak shift in the first cycle decreases (the impedance at -0.2 V vs Li / Li⁺ decreases by 40%).
[0065] Step F: Mix the passivated composite material with a conductive agent and a binder to prepare an electrode slurry.
[0066] Specifically, in Step F, the conductive agent is selected from acetylene black, SuperP or carbon nanofibers, and the binder is selected from PVDF, CMC or SBR.
[0067] It should be further noted that in Step F, the present invention designs the following scheme: Electrode paste formulation: Composite material: SuperP (conductive agent): PVDF (binder) = 8:1:1 (mass ratio), solvent NMP.
[0068] Mixing method: Planetary stirring (rotation speed 300 rpm, time 2 h) to ensure uniform dispersion.
[0069] Step G: Coat the electrode paste on the current collector, and perform drying and rolling processes to obtain a composite negative electrode sheet.
[0070] It should be further noted that in the said Step G, the present invention designs the following scheme: Sheet preparation: Coating thickness 100 μm (current collector is 10 μm copper foil), drying temperature 80 °C (vacuum environment), rolling compaction density 1.5 g / cm³.
[0071] It should be further noted that the present invention also designs an optimized scheme for the paste formulation: Mass ratio: Composite material: SuperP (conductive agent): PVDF (binder) = 8:1:1 (NMP solvent system).
[0072] Dispersion method: Planetary stirring (300 rpm × 4 h), viscosity controlled at 2000 - 3000 mPa·s (coating requirement).
[0073] It should be further noted that regarding the sheet preparation: Coating thickness: 120 μm (dry film thickness 100 μm, copper foil 10 μm).
[0074] Rolling density: 1.5 g / cm³ (porosity 25%, balancing energy density and rate performance).
[0075] Step H: Perform prelithiation treatment on the composite negative electrode sheet to improve the first Coulombic efficiency.
[0076] Specifically, in the said Step H, the prelithiation treatment adopts the direct contact method with lithium foil or lithium powder and is carried out under inert gas protection to improve the first Coulombic efficiency.
[0077] It should be further noted that in the said Step H, the present invention designs the following scheme: Prelithiation treatment: Contact the sheet with lithium foil (purity > 99.9%) under mechanical pressure (5 MPa) and let it stand for 12 h (Ar glove box).
[0078] Preferred values: 5 MPa pressure avoids the formation of lithium dendrites, and 12 h ensures sufficient reaction.
[0079] It should be further noted that the said method includes: Direct contact method: Purity of lithium foil: ≥99.9%, thickness 0.5 mm.
[0080] Pressure: 5 MPa (mechanical pressure, to avoid dendrite formation), pressure holding time 12 h (in an Ar glove box).
[0081] Effect: XPS shows that the proportion of LiF in SEI increases to 45% (only 30% in the traditional process), and the initial efficiency increases from 82% to 88%.
[0082] Step I: Assemble the prelithiated composite negative electrode sheet into a lithium-ion battery and conduct electrochemical performance tests.
[0083] Specifically, in the said Step I, the lithium-ion battery uses a liquid electrolyte or a solid electrolyte, and charge-discharge cycle tests, rate performance tests, and cycle life tests are conducted.
[0084] It should be further noted that in the said Step I, the present invention designs the following scheme: Battery assembly: CR2032 type half-cell, electrolyte 1 M LiPF6 / EC-DMC (1:1 vol%), counter electrode metallic lithium, test conditions: charge and discharge at 0.1 C to 5 C (voltage range 0.01 - 3.0 V).
[0085] Specifically, the said process uses a continuous production line, including a biomass raw material treatment module, a carbon nanotube growth module, a graphite composite module, a surface modification module, an electrode preparation module, and a battery assembly module.
[0086] It should be further noted that regarding the electrochemical test steps, the said scheme includes: Half-cell assembly: CR2032 type, electrolyte 1 M LiPF6 / EC-DMC (1:1 vol).
[0087] Test conditions: Charge-discharge curve: from 0.1 C (100 mA / g) to 5 C (5000 mA / g), voltage range 0.01 - 3.0 V.
[0088] Cycle life: capacity retention rate ≥85% after 1000 cycles (only 72% for the comparative sample).
[0089] Rate performance: capacity retention rate at 5 C is 91% (only 65% for the original graphite).
[0090] Furthermore, the design scheme of the said continuous production line includes: 1. Biomass raw material treatment module (Module 1) 1.1 Equipment composition Crushing unit: twin-shaft shear crusher (crushing particle size ≤2 mm).
[0091] Drying unit: Vacuum drying oven (temperature 105 ± 2 °C, vacuum degree -0.08 MPa, time 12 h).
[0092] Storage unit: Nitrogen-protected silo (water content ≤ 5%).
[0093] 1.2 Process flow 1. Raw material sorting (removing impurity metals) → 2. Crushing → 3. Vacuum drying → 4. Weighing and metering → 5. Conveying to the mixing unit.
[0094] 1.3 Key parameters Particle size of coconut shell raw material: d 50 = 1.5 mm (laser particle size analysis).
[0095] Moisture content after drying: 4.8 ± 0.2% (determined by Karl Fischer method).
[0096] 1.4 Production capacity: 1000 kg / h (continuous feeding, automatically adjusting the feeding speed when the moisture content fluctuation ≤ ±2%). 2. Carbon nanotube growth module (Module 2) 2.1 Core equipment Fluidized bed reactor (inner diameter 1.5 m, height 8 m).
[0097] Open hole rate of the distributor plate: 35 ± 2% (ensuring uniform distribution of the catalyst).
[0098] Temperature zone control: Three-zone heating (preheating zone / reaction zone / cooling zone).
[0099] 2.2 Process flow 1. Catalyst loading (impregnation with Fe(NO3)3·9H2O, loading amount 0.5 wt%) → 2. Drying (120 °C, 4 h) → 3. Carbonization pretreatment (N2 protection, heating to 600 °C, 2 h) → 4. CVD growth 2.3 Reaction parameters Gas flow rate ratio: CH4 / H2 / N2 = 1:2:7 (V / V).
[0100] Reaction temperature: 650 ± 5 °C (PID temperature control accuracy ±2 °C).
[0101] Growth time: 90 min (carbon nanotube yield: 25 ± 1%).
[0102] 2.4 On-line detection Laser dust particle counter (real-time monitoring of carbon nanotube concentration).
[0103] FTIR on-line monitoring (-OH group content ≤ 0.5% is qualified) 3. Graphite Composite Module (Module 3) 3.1 Key Equipment Double - helix conical mixer (rotation speed 20 rpm, filling coefficient 0.6).
[0104] High - speed shear disperser (power 55 kW, linear velocity 20 m / s).
[0105] Electrostatic eliminator (voltage ≤ 3 kV).
[0106] 3.2 Process Flow 1. Carbon nanotube pretreatment (nitric acid oxidation method, 65 °C, 2 h to generate - COOH) → 2. Coupling agent grafting (KH - 550, concentration 1 wt%) → 3. Mechanical mixing → 4. Ultrasonic - assisted dispersion.
[0107] 3.3 Core Parameters Carbon nanotube content: 10 wt% (XRF analysis, relative standard deviation RSD ≤ 1.5%).
[0108] Coating uniformity: CV value of carbon tube distribution observed by SEM ≤ 8% (area coverage rate 30 - 40%).
[0109] Dispersion time: ultrasonic power 400 W, 5 min (average particle size d 50 = 5.2 μm).
[0110] 3.4 On - line Monitoring Near - infrared spectroscopy (real - time detection of carbon tube distribution uniformity) and particle size distribution analyzer (D 90 / D 10 ≤ 3.0) are adopted.
[0111] 4. Surface Modification Module (Module 4) 4.1 Equipment Composition Plasma processor (frequency 13.56 MHz, power 3 kW).
[0112] Rotary coater (coating speed 0.5 m / min, accuracy ± 0.1%).
[0113] Vacuum drying oven (segmented temperature control: 80 °C / 2 h + 120 °C / 1 h).
[0114] 4.2 Process Flow 1. Corona treatment (voltage 15 kV, spacing 5 mm) → 2. Coating with silane solution (1 wt% KH - 550 ethanol solution) → 3. Vacuum drying.
[0115] 4.3 Key Control Points Surface energy improvement: contact angle ≤ 30° (measured by contact angle meter).
[0116] Grafting rate of chemical modification: The -NH2 content measured by FTIR is ≥ 2 mmol / g.
[0117] Thermal stability: TGA shows no mass loss below 200 °C.
[0118] 4.4 Production capacity: 200 m² / h (coating width 1.2 m).
[0119] 5. Electrode preparation module (Module 5) 5.1 Equipment configuration Double planetary mixer (revolution 50 rpm, rotation 300 rpm).
[0120] Slot coater (coating accuracy ±1.5%).
[0121] Infrared rapid drying furnace (with temperature zone segmented control).
[0122] 5.2 Process optimization Slurry ratio: Composite material: SuperP: PVDF = 8:1:1 (mass ratio, NMP system).
[0123] Viscosity control: Monitored by a rotational viscometer (40 °C, 2000 - 2500 mPa·s).
[0124] Coating thickness: Wet film thickness 150 ± 5 μm (dry film 100 ± 3 μm).
[0125] Drying curve: 80 °C × 2 min → 120 °C × 1 min (to avoid PVDF thermal decomposition).
[0126] 5.3 Quality control Coating areal density uniformity: RSD ≤ 3% (β-ray thickness gauge).
[0127] Bonding strength: 180° peel force ≥ 5 N / m (universal testing machine).
[0128] 6. Battery assembly module (Module 6) 6.1 Key processes Pole piece slitting (laser die cutting, burr height ≤ 5 μm).
[0129] Winding machine (tension control ±0.5 N).
[0130] Laser welding (stainless steel shell, penetration depth 0.2 - 0.3 mm).
[0131] Laser injection (injection accuracy ±0.5 μL).
[0132] 6.2 Prelithiation treatment Pressure control: Servo press (holding pressure 5.0 ± 0.1 MPa for 12 h).
[0133] Impedance monitoring: EIS test (Li⁺ diffusion coefficient increased by 3 times).
[0134] First efficiency detection: constant current charge and discharge (first cycle efficiency at 0.1C ≥ 88%).
[0135] 6.3 Finished product testing Thickness deviation: ≤ ±0.1 mm (fully inspected with micrometer).
[0136] Voltage consistency: CV difference < 3 mV within 100 pcs.
[0137] Continuous production line connection design 1. Inter-module transfer uses Negative pressure pneumatic conveying (particle size > 200 mesh).
[0138] Lifting and translation mechanism (docking accuracy ±0.5 mm) Enclosed conveyor belt (temperature and humidity control ±5%RH).
[0139] 2. Optimization of core connection points is shown in Table 1: Table 1 Optimization of core connection points Advantage data of continuous production 1. Production efficiency: ≥ 200 kg / 8-hour work system (traditional batch method < 50 kg / day).
[0140] 2. Quality stability: CV value between batches < 5% (traditional process > 15%).
[0141] 3. Energy consumption index: energy consumption per unit product ≤ 0.8 kWh / kg (42% lower than traditional).
[0142] 4. Degree of automation: PLC full-process control (OEE overall equipment efficiency ≥ 90%).
[0143] Key nodes of quality control 1. Raw material control: moisture content of biomass < 5% (alarm threshold of on-line moisture meter).
[0144] 2. Process control: temperature fluctuation of CVD reactor ±2°C (PID automatic regulation).
[0145] 3. Final inspection standard: laser particle size d 50 = 12 ± 0.5 μm (laser diffractometer).
[0146] This continuous production solution solves the instability problem of the batch process through modular design and intelligent control, realizes the stable production of carbon nanotube / graphite composite negative electrode materials, and meets the needs of large-scale power batteries.
[0147] It is understandable that by adopting the modular design of the production line, the continuous processing capacity reaches 5 kg / h, meeting the industrial requirements.
[0148] The technical features described above can be combined arbitrarily. Although not all possible combinations of these technical features are described, any combination of these technical features should be considered to be covered by this specification as long as such a combination is not contradictory.
[0149] The specific embodiments of the present invention described above do not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and deformations made according to the technical concept of the present invention should be included within the protection scope of the claims of the present invention.
Claims
1. Preparation process of a composite anode material of biomass-based carbon nanotubes and natural graphite, characterized in that It includes the following steps: Step A: Mix the biomass raw material with the catalyst precursor and then carry out carbonization treatment to obtain biomass-based carbon nanotubes; Step B: Mix the biomass-based carbon nanotubes with natural graphite, and use an in-situ growth process to coat the carbon nanotubes on the surface of graphite particles; Step C: Carry out surface modification treatment on the coated composite material to improve the interfacial bonding force between the carbon nanotubes and graphite; Step D: Use a low-temperature heat treatment process to optimize the pore structure of the composite material to improve the lithium-ion diffusion rate; Step E: Carry out surface passivation treatment on the heat-treated composite material to reduce irreversible lithium-ion consumption; Step F: Mix the passivated composite material with a conductive agent and a binder to prepare an electrode slurry; Step G: Coat the electrode slurry on a current collector and carry out drying and rolling treatments to obtain a composite negative electrode sheet; Step H: Carry out prelithiation treatment on the composite negative electrode sheet to improve the first Coulombic efficiency; Step I: Assemble the prelithiated composite negative electrode sheet into a lithium-ion battery and carry out electrochemical performance tests.
2. The preparation process of the biomass-based carbon nanotube and natural graphite composite anode material according to claim 1, characterized in that, In the said Step A, the biomass raw material is selected from coconut shells, lignin, straws or fruit shells, and the catalyst precursor is selected from oxides or salts of iron, cobalt or nickel.
3. The preparation process of the biomass-based carbon nanotube and natural graphite composite anode material according to claim 2, characterized in that, In the said Step B, the in-situ growth process uses chemical vapor deposition, and a carbon source gas and a carrier gas are introduced, and carbon nanotube growth is carried out at 500 - 800 °C. The carbon source gas includes methane and / or ethane, and the carrier gas includes hydrogen and / or argon.
4. The preparation process of the biomass-based carbon nanotube and natural graphite composite negative electrode material according to claim 1, characterized in that, In the said Step C, the surface modification treatment uses plasma treatment or silane coupling agent modification to improve the interfacial bonding force between the carbon nanotubes and graphite.
5. The preparation process of the biomass-based carbon nanotube and natural graphite composite anode material according to claim 4, characterized in that, In the said Step D, the temperature of the low-temperature heat treatment process is 400 - 600 °C, and it is carried out under the protection of an inert gas to optimize the pore structure and reduce structural collapse.
6. The preparation process of the biomass-based carbon nanotube and natural graphite composite negative electrode material according to claim 1, characterized in that, In the said Step E, the surface passivation treatment uses chemical vapor deposition to deposit an amorphous carbon or graphene protection layer to reduce side reactions of the electrolyte.
7. The preparation process of the biomass-based carbon nanotube and natural graphite composite anode material according to claim 1, characterized in that, In the said Step F, the conductive agent is selected from acetylene black, SuperP or carbon nanofibers, and the binder is selected from PVDF, CMC or SBR.
8. The preparation process of the biomass-based carbon nanotube and natural graphite composite anode material according to claim 1, characterized in that, In the said Step H, the prelithiation treatment uses the direct contact method of lithium foil or lithium powder and is carried out under the protection of an inert gas to improve the first Coulombic efficiency.
9. The preparation process of the biomass-based carbon nanotube and natural graphite composite anode material according to claim 1, characterized in that, In the said Step I, the lithium-ion battery uses a liquid electrolyte or a solid electrolyte, and charge-discharge cycle tests, rate performance tests and cycle life tests are carried out.
10. The preparation process of the biomass-based carbon nanotube and natural graphite composite negative electrode material according to claim 1, characterized in that, The said process uses a continuous production line, including a biomass raw material treatment module, a carbon nanotube growth module, a graphite composite module, a surface modification module, an electrode preparation module and a battery assembly module.
Citation Information
Patent Citations
Graphite negative material of lithium-ion battery and preparation method of negative material
CN103199254A
Hybrid carbon nanotube and graphene nanostructures
CN106163980A
Composite negative electrode material, preparation method thereof and lithium ion battery
CN117832463A
Composite material and preparation method thereof
CN118703018A
Graphite negative electrode material and preparation method thereof, and secondary battery
CN119695107A